Do forward markets enhance competition? Experimental evidence - Chloé Le Coq; Henrik Orzen (Stockholm School of Economics, The Economic Research Institute (EFI), 2002)
Hedging risks is an important rationale for the existence of forward markets. However, Allaz and Vila (1993) show that duopolists can also have a strategic motive to sell forward, irrespective of exogenous uncertainties. Moreover, in their model the possibility of forward trading increases competitiveness between the two firms, raising consumer surplus and welfare. In this study we analyze the case of an n firm oligopoly in Allaz' and Vila's framework and derive comparative static predictions with regard to the market institution and the number of competitors. We then test the theoretical hypotheses in a laboratory experiment. Our findings support the main comparative-static predictions of the model but also suggest that, when compared to the increase in competitive pressure due to entry, the competition-enhancing effect of a forward market is weaker than predicted.
Keywords: C72; C92; D43; L13; 330; Cournot Competition; Forward Markets; Spot Markets; Experiments; Duopol; Termingeschäft; Test; Theorie